N,N'-diisopropylthiourea and N,N'-dicyclohexyl-thiourea zinc(II) complexes as precursors for the synthesis of ZnS nanoparticles - N. Moloto; N. Revaprasadu; M.J. Moloto; P. O'Brien; J. Raftery (South African Journal of Science, 2010)
The single X-ray crystal structures of zinc (II) complexes of N,N'-diisopropylthiourea and N,N' dicyclohexylthiourea weredetermined.These complexes, similar to other alkylthioureas, were found to be effective as precursors for the preparation of hexadecylamine-capped ZnS nanoparticles. The complexes are air-stable, easy to prepare and inexpensive. They pyrolyse cleanly to give high-quality ZnS nanoparticles, which show quantum confinement effects in their absorption spectra and close to band-edge emission. Their broad diffraction patterns are typicalof nanosized particles while their transmission electronmicroscopy images showed agglomerates of needle-like platelet nanoparticles.